Climate change, mobility and security: Insights from econometric analyses across fragile regions - Mastrorillo, Marina; Villa, Victor; Belli, Anna; Pacillo, Grazia (2025)
Climate change is a growing driver of insecurity, displacement, and vulnerability in fragile and conflict-affected regions (Bellemare, 2015; Collier, 2008; Freeman, 2017; Schlenker & Lobell, 2010), disproportionately affecting poor, agriculture-dependent communities, displaced populations, and their hosts (Läderach et al., 2021; UNHCR, 2024). By 2040, the number of countries facing extreme climate-related hazards is projected to rise from three to 65, most of which host displaced people (Craparo et al., forthcoming). This policy brief summarizes econometric findings from six econometric studies in Nigeria, Kenya, Jordan, Mali, Ethiopia, and the Horn of Africa. Using datasets such as DHS, IOM’s DTM, and UNHCR surveys, combined with climate, price, and conflict data, the studies examine links between climate variability, mobility, malnutrition, and resilience. Methods include Structural Equation Modeling, Difference-in-Differences, Propensity Score Matching, and spatial techniques. The findings highlight the urgency of integrated, evidence-based responses to climate risks in fragile settings.